Direct Restorations, Endodontics, and Bleaching: Materials and Techniques Used by General Dentists of New Zealand. (7th March 2019) - Loch, Carolina; Ratnayake, Jithendra; Veerasamy, Arthi; Cathro, Peter; Lee, Robert; Brunton, Paul A.
Abstract : Background . To investigate the selection and use of direct restorative materials, endodontic techniques adopted, and approaches to bleaching by general dentists in New Zealand. Methods . A questionnaire comprising 19 sections and 125 questions was distributed via mail to 351 general dentists in New Zealand who were selected, at random, from the Dental Council of New Zealand's 2016 register. Results . A total of 204 questionnaires were returned, of which 188 were usable. Direct resin composite was the most commonly used material for occlusoproximal cavity restorations in premolars (93.7%) and permanent molars (85.2%). Resin-modified glass ionomer cements (34%) and resin composite materials (31.4%) were more commonly used in the restoration of deciduous molars. Home-based vital bleaching was provided by a significant number of dentists (86%), while only 18% provided practice-based bleaching. Cold lateral condensation was the most commonly used obturation technique (55.8%), and 83% of respondents reported using rubber dam for treatments. Conclusions . The findings from this study indicate that dentists in New Zealand are adapting to new materials and technologies to provide high quality care to their patients. Aesthetic treatments such as bleaching have become an integral part of general dental practice.